2014
DOI: 10.1177/0960327113504972
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical changes and oxidative stress induced by zearalenone in the liver of pregnant rats

Abstract: The aim of the present research was to examine the toxic influence of different doses of zearalenone (ZEN) on the liver, especially oxidative stress induced by ZEN on the liver. A total of 48 pregnant Sprague-Dawley rats were randomly assigned into 4 treatments groups with 12 animals in each. The rats were fed with a normal diet treated with 0 mg/kg (control), 50 mg/kg (treatment 1), 100 mg/kg (treatment 2), or 150 mg/kg (treatment 3) ZEN in feed on gestation days (GDs) 0–7 and then all the rats were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
16
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 49 publications
3
16
0
Order By: Relevance
“…Our study indicated that ZEA induced oxidative stress in testicular tissue as manifested by the modulation of GSH systems (GPx, GR and GST enzymes and GSH/GSSG levels). These results concurred with previous studies [8,9,43,44]. Importantly, GST expression in testes was not modified and the activity of this enzyme was inhibited.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our study indicated that ZEA induced oxidative stress in testicular tissue as manifested by the modulation of GSH systems (GPx, GR and GST enzymes and GSH/GSSG levels). These results concurred with previous studies [8,9,43,44]. Importantly, GST expression in testes was not modified and the activity of this enzyme was inhibited.…”
Section: Discussionsupporting
confidence: 93%
“…Therefore, these interleukins at pathological concentrations in the testis may injure the seminiferous epithelium, elevate the sensitivity and trigger some inflammation [49]. In accordance with the present findings, previous studies showed that exposure to ZEA also induced an intense inflammatory reaction as manifested [43][44][45]. These effects may help explain that the testicular immune structure could be disturbed by mycotoxins, such as ZEA.…”
Section: Discussionsupporting
confidence: 89%
“…Previous studies show that ZEA exists in the contaminated livestock feed and food, and potentially impacts human and animal health [ 39 – 43 ]. For domestic animals, ZEA seriously interferes with their reproduction [ 40 – 42 ] and induces oxidative stress as a result of decreased antioxidative enzymes [ 44 , 45 ]. However, no detailed information regarding ROS induced by ZEA in porcine granulosa is available, and the rescue of the oxidative stress has not been attempted.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, different reports have demonstrated that ZEN induces ROS production (Bouaziz et al 2009;Jia et al 2014;Zhou et al 2015) and lipid peroxidation in vitro and in vivo and can engender oxidized DNA bases (Abid-Essefi et al 2004;Hassen et al 2007;Abbes et al 2007). Results of our study provide evidence that ZEN triggers ROS generation in HCT116 and HEK293 cells.…”
Section: Discussionmentioning
confidence: 99%